PENGARUH SERVICE QUALITY DAN SOCIAL INTERACTION TERHADAP PURCHASE INTENTION - Yuni Elisa Suyani; Verina Halim Secapremana (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2021)
The study was conducted to determine the magnitude of the interaction effect on buying interest. So that it can improve customer service and buying interest. Interactions are measured by service quality and social interaction, using customer satisfaction and customer trust as a bridge to increase purchase intention. Research respondents were 160 active customers of PT Prudential Life Assurance. The study used a qualitative approach and used the SEM method on AMOS for data processing. It was found that Service Quality had an effect on purchase intention. while Social Interaction does not fully affect Purchase Intention directly. More effort is needed to build relationships, which can be done by giving customers more time to interact and respond. So that there is trust in the internal relationships between agents and customers.